Effects of Rejection by a Friend for Someone Else on Emotions and Behavior - Rajchert, Joanna; Żółtak, Tomasz; Szulawski, Michał; Jasielska, Dorota (Frontiers in Psychology, 2019)
Studies show that rejection increases negative affect and aggression and decreases helping behavior toward the excluder. Less is known about emotions and behavior after rejection by a friend for someone else. In two experimental studies (N = 101 and N = 169), we tested the predictions that rejection would feel worse in a close relationship but would result in less aggression and more reconnecting behavior, especially when the reasons for rejection were unknown. The results of Study 1 showed that, as expected, among acquaintances, more aggression was noted only after comparative rejection, but among strangers, aggression was also observed after rejection with no stated reason. Negative feelings toward a new acquaintance were only marginally stronger than those toward a stranger in Study 1, but Study 2 confirmed that rejection by a best friend, and especially comparative rejection by a friend, felt worse than other conditions. Study 2 also showed that reconnecting behavior was more likely to dominate over aggressive behavior between people in close relationships than between strangers. The results are discussed mostly in light of the multimotive model of rejection.